The athletic musician: A guide to playing without pain - Paull, Barbara; Harrison, Christine (Boston Scarecrow Press, 1997)
The Athletic Musician is an innovative approach that teaches musicians how to prevent and manage injuries, presented in a unique format that combines sound medical protocol with a musician's point of view. Harrison, a musician, discusses the magnitude of the problem of musicians' injuries with reference to statistical surveys and discusses the emotional and psychological impact of injury on the individual musician. Paull, an orthopedic physiotherapist describes, in layman's terms, the athletic approach to a musician's injuries. Each commonly injured area is examined in turn, from neck, back and shoulder pain to arm, wrist and hand problems. For each area, the anatomy is described, followed by an explanation of what causes the injury and how to avoid or prevent the injury from occurring.Musicians should regard themselves as elite "musical athletes" and protect themselves from injury by following athletic training protocols. The authors present appropriate stretching regimes and postural corrections for both on and off stage, as well as ergonomic changes to instrument and playing positions. The text is amply illustrated with sketches for every exercise and stretch, photographs of musicians demonstrating playing postures, and unique anatomical drawings of musicians.